Enrichment of acid-tolerant sulfide-producing microbes from an acidic pit lake - Liu, Yutong; Macalady, Jennifer L.; Sánchez-España, Javier; Burgos, William D. (Frontiers in Microbiology, 2024)
High concentrations of harmful metal(loid)s and extreme acidity are persistent environmental concerns in acidic pit lakes. In this study, we examine Cueva de la Mora (CM), a meromictic pit lake in the Iberian Pyrite Belt, Spain, as a model system. Our research aims to explore potential bioremediation strategies to mitigate the impacts of metal(loid)s and acidity in such environments. The major strategy applied in this research is to biologically stimulate sulfate reduction (i.e. biosulfidogenesis) in the deep layer of the lake to promote the formation of lowsolubility sulfide minerals. Previous omics-based studies of CM have shown that several sulfatereducing bacteria (SRB) taxa are present in the deep layer. However, their activities are likely limited by the availability of electron donors for sulfide production. Therefore, different amendments (glycerol, elemental sulfur, and glycerol + elemental sulfur) were tested to promote sulfide production and enrich acid-tolerant sulfide-producing microbes. Our results showed that glycerol stimulated dissimilatory sulfate reduction much faster than elemental sulfur alone, suggesting that electron donor limitations control sulfide production. Furthermore, the combined addition of glycerol and elemental sulfur (S(0)) resulted in the highest level of sulfide production. This indicates that S(0) can play a significant role as an electron acceptor in further promoting sulfide production when a suitable electron donor is present. Microbial community analysis revealed that Desulfosporosinus acididurans, a previously discovered acid-tolerant SRB, was enriched and became the dominant species in incubations with glycerol only ( 76-96% abundance) or the combination of glycerol and S(0) ( 93-99% abundance).